The Effects of Cymbopogon citratus (lemon grass) on Morphine Withdrawal Signs in Male Mice - Hamed Ahmadi Sheikh-Sarmast; Saeid Abbasi-Maleki * (Herbal Medicines Journal, 2018)
Background and Aim: The antispasmodic, analgesic, antioxidant, anti-inflammatory and sedative effects of Cymbopogon citratus (C. citratus) have been already examined in various studies. Hence, the present study was conducted to investigate the effect of C. citratus hydroalcoholic extract on morphine withdrawal signs in male mice.